Silver Nanoparticles Synthesis by Hamza's Khubdat (A.S.) (Kombucha) Tea and used in Burn Wounds Treatment - Esam J. Al-Kalifawi (Journal of Global Pharma Technology, 2018)
In the present study, silver nanoparticles were synthesized using Hamza's Khubdat (A.S.) tea as the reducing and capping agent. The nanoparticles were characterized using UV-visible, FT-IR, XRD, and SEM methods. The surface plasmon resonance peaks in absorption spectra for silver colloidal solution showed an absorption peak at 340 nm in a UV-visible spectrum. Several peaks were observed indicating the Hamza's Khubdat (A.S.) tea is composed of various functional groups which include vibration of amine groups responsible for the silver nanoparticles formation were characterized by FT-IR. The XRD results suggested that the crystallization of the bio-organic phase occurs on the surface of the silver nanoparticles or vice versa. The broadening of peaks in the XRD patterns was attributed to particle size effects and the average particles size about 29.15 nm. The silver nanoparticles synthesized by using Hamza's Khubdat (A.S.) tea were scanned using SEM. It reveals that a silver nanoparticle seems to be spherical in morphology. In addition, antimicrobial packaging was prepared by mixing colloidal silver nanoparticles synthesized by Hamza's Khubdat (A.S.) tea with nanocellulose pellicle of Hamza's Khubdat (A.S.) and depositing this hybrid coating (NCP/Ag) as a layer. The NCP/Ag coated layer were then characterized by scanning electron microscopy (SEM), furthermore study their antimicrobial activity. SEM showed deposition of Ag nanoparticles on the surface of NCP and formation of a relatively smooth, dense coating layer on the pellicle surface. The results also demonstrated that the NCP /Ag coating exhibited good antibacterial activity against four Gram-negative and four Gram-positive bacteria which causing burn wounds inflammation.Keywords: Hamza's Khubdat (A.S.), Silver nanoparticles, Nanocellulose pellicle, Antimicrobial activity, pathogenic bacteria.